Differences in the International Competitiveness of Greece and Germany in the Context of Greece’s Public Debt Crisis (Economic and Political Thought, 2014)
The article aims to discuss the international competitiveness of Greecein comparison with Germany, the Eurozone and the European Union asa whole in the context of Greece’s public debt crisis. The first part evokes thedefinition of international competitiveness that is quoted in literature. Takinginto account the fact that competiveness cannot be presented as a singlefigure, the author analyses a series of macro-economic indicators connectedwith trade in goods and services and unit labour costs and he examines thelevel of inflation and unemployment as well as the share of public debt andbudget balance in the GDP of selected countries of the Eurozone and theEuropean Union. In addition, the position of Greece and Germany in theinternational competitiveness rankings and the GDP growth indicators arepresented. The analysed data show that the international position of Greekeconomy is much lower than that of Germany. As it could have been expected,the situation was worsened by the global economic crisis of 2008, whichdemonstrated the weakness of Greece while it only upset the internal balancein Germany. Despite Germany’s problems with maintaining public debt andbudget deficit in relation to the GDP at the level specified by the Stabilityand Growth Pact, these did not have a bad impact on the balance of currentturnover and a drastic increase in the unemployment level in the country.The competitive position of Germany measured by various competitivenessrankings did not change either and is much better than Greece’s.